Genetic polymorphisms of the CDC27 gene are associated with susceptibility and outcomes of non-syndromic congenital heart disease: a bi-ethnic case–control study in Chinese populations - Yuan, Teng; Zhu, Feng; Aisan, Aikebai; Maheshati, Tunike; Li, Yunxia; Tian, Ren; Chen, You (Frontiers in Genetics, 2026)
BackgroundCell division cycle 27 (CDC27) gene expression is closely associated with the cell cycle and has been implicated in the pathogenesis of congenital heart disease (CHD) in animal models. This study focuses on investigating whether single-nucleotide polymorphisms (SNPs) in the CDC27 gene are associated with CHD and the cardiac remodeling process in the population of Xinjiang, China.MethodsThis study conducted a case–control study including 689 controls and 575 patients with CHD. SNPs of the CDC27 gene were genotyped using an improved multiple ligase detection reaction.ResultsOur study found that the CDC27 rs11570579 polymorphism was significantly associated with CHD susceptibility in the Uyghur population (additive model: aOR = 0.66, p = 0.029; dominant model: aOR = 0.80, p = 0.038), but not in the Han population. The rs11570488 GA genotype was associated with higher pulmonary artery systolic pressure (PASP), more severe cardiac remodeling, and increased long-term mortality in both ethnic groups (all p < 0.001), with the mortality difference being significant only in patients with pulmonary hypertension. Haplotype analysis identified ethnic-specific haplotypes associated with CHD susceptibility and elevated PASP.ConclusionThe CDC27 rs11570579 polymorphism is associated with susceptibility to CHD in the Uyghur population of Xinjiang. The rs11570488 polymorphism is associated with PASP, cardiac remodeling, and long-term mortality in patients with CHD.